A City for the Few: A Marxist Criticism Analysis of Class Struggles and Ideology in Zootopia (2016) Movie - Tumiwa, Tessalonika Putri Gracia; Gumanti, Priscilla Aurellia Fensa; Tarihora, Gracia Isabela Sabathini; Syah, Caleb Joshua (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2026)
Through the lens of Marxist criticism, this study investigates class struggle and ideology as depicted in the 2016 animated feature Zootopia. It aims to reveal how constructed ideologies contribute to shaping class struggles and how false ideologies. The film, which portrays a society divided into predators and prey, was examined to understand how labor exploitation and ideological dominance reflect Karl Marx's and Engel's Marxist theory (1847 & 1867). Qualitative methodology was employed in this study, with data collection focusing on the examination of particular scenes, spoken dialogue, and various cinematic elements: camera positioning, lighting design, and musical accompaniment. As the results: 1) Class Divisions: the film illustrates how societal ideologies, particularly the